Heavy metals in the bottom sediments of the Sasyk estuary - Shuraiev, Ihor; Kulaha, Tetiana; Paryshev, Oleksander (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Purpose. The main aim of research is to study the bottom sediments of the Sasyk estuary, in particular, to establish their lithological characteristics and the peculiarities of the distribution of heavy metals in their layers. Method. The research was done with the results of the expedition work carried out in 2018-2019, 31 samples of the bottom sediments of the Sasyk estuary, channels and paleochannels of the Kogylnyk and Sarata rivers, and rocks of the shoreline of the studied reservoir were selected. We carried out sampling along the network of 31 stations from a motor boat using a bottom-grab and orientation by GPS navigation. The content of heavy metals was determined using geochemical spectral emission analysis. Statistical and cartographic processing of the research results was carried out using geographic information systems Mapinfo, QGIS, Global Mapper and Surfer. Also, to establish the possible routes of metal migration, we used the analysis of mesotopolineaments formed according to the NASA SRTM digital terrain model, with the construction of rose diagrams of the main directions of the lineaments. The results. We established that the bottom sediments were represented mainly by grey-black, black, viscous silt, often with an admixture of shell detritus. Less often, they were composed of sand, sometimes muddy with abundant fauna. We also determined the content of heavy metals in the system of bottom sediments, features of their distribution and possible ways of infusing. Thus, in the territory of the Sasyk estuary, heavy metals of the first (Pb), second (Ni, Cu, Cr, Mo) and third (V, Mn, Ba) hazard class are found in high concentrations. The average content of Pb for the bottom sediment system of the estuary is: for sand – 32 mg/kg, for silt – 41 mg/kg. The maximum content for both is 100 mg/kg. The average Ni content is: for sand – 27 mg/kg, for silt – 62 mg/kg. The maximum content for sand is 80 mg/kg, for silt – 100 mg/kg. The average Cu content in the silt of the Sasyk estuary is 81 mg/kg, and 26 mg/kg in the sand. An elevated content of Mn, Ba and Mo was also found in several samples. Оften areas with increased concentrations of metals have a point character. In almost all cases, they are connected to the river systems adjacent to the pond. The distribution of some metals is correlated with the main directions of estuary water circulation. Wastewater is a likely sources of metals entering the estuary geoecosystem. We also assume that the migration of these elements to the pond may occur through tectonic blocks. Scientific novelty. For the first time in recent years, we have carried out expeditionary work on research of the bottom sediments of the Sasyk estuary, along the complete network of the station. We obtained the data on the gross content of heavy metals, and determined their average, maximum and minimum concentrations. For the first time, maps of the spatial distribution of metals were constructed, which made it possible to establish the main regularities of their accumulation in the bottom sediment system of the pond. Practical significance. Pollution of the bottom sediments of the Sasyk estuary with heavy metals is one of the components of today’s critical ecological state of the pond, which affects the well-being of the residents of the surrounding areas. The obtained results can be used at the state level to create effective programs for quality management of the resource potential of the estuary.